(untitled) (GYMNASIUM, 2009)
If tourism constitutes the “ activities of persons traveling”, it would follow that a tourist is the individual who actually does the traveling outside his or her home community. At the simple level this is correct, but the defining characteristic of a tourist is not just the travel component Tourism, the world,s largest industry, is composed of many segments, including transportation; accommodations; attractions; and the government and nongovernmental agencies responsible for planning, setting policy, and marketing. A tourist is defined in this chapter as a leisure traveler. Sport tourism is defined as travel to participate in sport, to watch sport, or to venerate something or somebody associated with a sport.